PENERAPAN PEMBELAJARAN BERBASIS STEM UNTUK MENINGKATKAN LITERASI SAINS SISWA KELAS V SEKOLAH DASAR PADA MATERI BERKENALAN DENGAN BUMI - Tri Fadillah; Vania agustin; Neni Hermita; Rifqa Gusmida Syahrun Barokah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Scientific literacy is a basic skill that students need to have to face the challengesof the 21st century. This study aims to analyze the improvement of scientific literacyof fifth-grade elementary school students through the implementation of Science,Technology, Engineering, and Mathematics (STEM)-based learning on the topic"Getting to Know the Earth". This type of research is quantitative with a pre-experimental design with a one-group pretest-posttest design. The sample of thisstudy consisted of 32 fifth-grade students of SDN 042 Pekanbaru who were selectedusing a purposive sampling technique. The data collection instrument was amultiple-choice scientific literacy test that covered the dimensions of PISA scientificliteracy. Data analysis used the average test and the Normalized Gain (N-Gain)formula. The results showed an average pretest score of 89.06 and increased to91.25 in the average posttest score. The N-gain analysis showed an increase of0.20 which is included in the low category. The low N-gain score is caused by theceiling effect because the students' initial scores were already very high, so the roomfor score improvement is limited. Overall, the implementation of STEM-basedlearning through the “artificial rain” experiment has a positive impact instrengthening students' understanding of scientific concepts and literacy in ameaningful way.